EVALUATION OF THE PRESENCE OF NITRATE AND ITS REMOVAL FROM GROUNDWATER SOURCES IN MARINGÁ-PR - Rezende, Driano; Mantovani, Daniel; Valim Junior, Nilton Carlos; Bergamasco, Rosângela; Nishi, Leticia; Samuelsson, Evelin; Cavalcante , Edson Rodrigues (Revista Científica da Faculdade de Educação e Meio Ambiente, 2020)
Regarding groundwater quality, the presence of nitrate is among the main indicators of water pollution. The aim of the present study was to evaluate the presence of nitrate, verify the hydrochemical standard and evaluate the efficiency of the removal process of nitrate ions by activated carbon from groundwater sources of Ribeirão Borba Gato (BHBG). The samples were collected between the period of 08/2014 to 08/2015, in 19 deep tub wells and subjected to some physical-chemical analyzes and treated with activated carbon filter. Our results shows that was possible to know the hydrochemical standard of water collected in the study area, identify possible risks of anthropogenic contamination, through the nitrate concentrations and also the amount of nitrate that the commercial activated carbon filter retains in slow filtration process. Most samples showed nitrate concentrations above the natural value of groundwater. So one can see that the underground sources of BHBG has suffered contamination and other pollutants may have equal or greater hazard to human health and environmental.